Collaborative interactions between neutrophil elastase and metalloproteinases in extracellular matrix degradation in three-dimensional collagen gels - Zhu, Yunkui (BioMed Central, 2001)
BACKGROUND: Extended culture of monocytes and fibroblasts in three-dimensional collagen gels leads to degradation of the gels (see linked study in this issue, "Fibroblasts and monocytes contract and degrade three-dimensional collagen gels in extended co-culture"). The current study, therefore, was designed to evaluate production of matrix-degrading metalloproteinases by these cells in co-culture and to determine if neutrophil elastase could collaborate in the activation of these enzymes. Since co-cultures produce prostaglandin E(2) (PGE(2)), the role of PGE(2) in this process was also evaluated. METHODS: Blood monocytes from healthy donors and human fetal lung fibroblasts were cast into type I collagen gels and maintained in floating cultures for three weeks. Matrix metalloproteinases (MMPs) were assessed by gelatin zymography (MMPs 2 and 9) and immunoblotting (MMPs 1 and 3). The role of PGE(2) was explored by direct quantification, and by the addition of exogenous indomethacin and/or PGE(2). RESULTS: Gelatin zymography and immunoblots revealed that MMPs 1, 2, 3 and 9 were induced by co-cultures of fibroblasts and monocytes. Neutrophil elastase added to the medium resulted in marked conversion of latent MMPs to lower molecular weight forms consistent with active MMPs, and was associated with augmentation of both contraction and degradation (P < 0.01). PGE(2) appeared to decrease both MMP production and activation. CONCLUSION: The current study demonstrates that interactions between monocytes and fibroblasts can mediate tissue remodeling.